Recherches sur la transitude au Québec : entre absence et exploitation des savoirs trans - Clark Pignedoli; Maxime Faddoul (Genre, Sexualité et Société)
From the methodological perspective of autoethnography, this article examines how trans people are exploited as precarious workers in neoliberal academia. It highlights the double dynamic of erasure and exploitation of trans people “as trans” in research. We show how transness, once extracted as value within a biocapitalist context, can participate in the processes of wealth accumulation, and thus how trans people’s working conditions within academic research come to be overdetermined by specific mechanisms of extractivism. In conclusion, we share some resistance strategies that help counter these dynamics.